Coronavirus Occurrence in the Household Influenza Vaccine Evaluation (HIVE) Cohort of Michigan Households: Reinfection Frequency and Serologic Responses to Seasonal and Severe Acute Respiratory Syndrome Coronaviruses. (23rd March 2021) - Petrie, Joshua G; Bazzi, Latifa A; McDermott, Adrian B; Follmann, Dean; Esposito, Dominic; Hatcher, Christian; Mateja, Allyson; Narpala, Sandeep R; O'Connell, Sarah E; Martin, Emily T; Monto, Arnold S
Abstract: Background: We investigated frequency of reinfection with seasonal human coronaviruses (HCoVs) and serum antibody response following infection over 8 years in the Household Influenza Vaccine Evaluation (HIVE) cohort. Methods: Households were followed annually for identification of acute respiratory illness with reverse-transcription polymerase chain reaction–confirmed HCoV infection. Serum collected before and at 2 time points postinfection were tested using a multiplex binding assay to quantify antibody to seasonal, severe acute respiratory syndrome coronavirus (SARS-CoV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike proteins and SARS-CoV-2 spike subdomains and N protein. Results: Of 3418 participants, 40% were followed for ≥3 years. A total of 1004 HCoV infections were documented; 303 (30%) were reinfections of any HCoV type. The number of HCoV infections ranged from 1 to 13 per individual. The mean time to reinfection with the same type was estimated at 983 days for 229E, 578 days for HKU1, 615 days for OC43, and 711 days for NL63. Binding antibody levels to seasonal HCoVs were high, with little increase postinfection, and were maintained over time. Homologous, preinfection antibody levels did not significantly correlate with odds of infection, and there was little cross-response to SARS-CoV-2 proteins. Conclusions: Reinfection with seasonal HCoVs is frequent. Binding anti-spike protein antibodies do not correlate with protection from seasonal HCoV infection. Abstract : Reinfection with seasonal coronaviruses was frequent over 8 years. Anti-spike protein binding antibody levels to seasonal coronaviruses were high, with little increase postinfection, and were maintained over time. These antibodies did not correlate with protection from infection.